New virtual educational reality, a view from the perspective of higher education teachers - Rodríguez Aguilar, Adriana Daniela; González Holguín, María de los Ángeles (IE Revista de Investigación Educativa de la REDIECH, 2025)
As a result of the pandemic, higher education institutions had to implement a virtual educational model, aimed at the use of ICT, which allows teaching and learning in different scenarios. This research aimed to analyze the elements contemplated by the new virtual educational reality, from the perspective of higher education teachers, based on virtual learning environments, motivation, and integral education. The methodology was developed in three stages: a) design, scope, and sample population; b) application of the instrument; c) frequency, comparative, correlational, and factor analysis. Under these conditions, the most outstanding results indicate that virtual learning environments are more related to the factors of integral education than to motivation, but the circumstances lead that, to overcome the active methodologies, use of ICT and class planning, it is necessary to consider the social reinforcement of students and the use of playful activities.